PERAN BRAND IMAGE MEMEDIASI PENGARUH COUNTRY OF ORIGIN TERHADAP PURCHASE INTENTION PRODUK MEREK WARDAH - Pradnyasari, Putu Dian; Aksari, Ni Made Asti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
The growth of cosmetics industry in Indonesia is attributed to the changes in people's lifestyles. This study aims to examine the role of brand image as a mediator between country of origin and purchase intention towards Wardah cosmetics. Research data was collected by distributing questionnaires to 120 respondents in Denpasar, Bali and analyzed using path analysis. The results of this study show that country of origin has a positive and significant effect on both brand image and purchase intention, and purchase intention is positively influenced by brand image. It was also found that the relationship between country of origin and purchase intention is partially mediated by brand image. This research implies that when consumers have positive perceptions of a product’s country of origin, it will create a positive brand image which in turn will affect the consumers’ purchase intention towards that product.